Dermatoglyphs and chromosome mosaicism in parents of children with trisomy 18. Issue 2 (April 1980) - Holmes-Siedle, M; Kerr, S; Lindenbaum, R H; Bobrow, M
Abstract : Parents of patients with Down's syndrome show dermatoglyphic features intermediate between the affected and the normal population. Dermatoglyphs were studied on the parents of 19 cases of trisomy 18, but no similar "intermediate" traits were discovered. The number of cases studied needs to be enlarged before it can definitely be stated that trisomies 18 and 21 differ in this respect.